Intensivierung, Privatisierung, Relativierung: Muster religiösen Wandels bei Geflüchteten - Nagel, Alexander-Kenneth (Zeitschrift für Religion, Gesellschaft und Politik, 2022)
As far as migration studies address religion at all, they tend to consider it from a vantage point of intensification or radicalization. At the same time, other options of religious change, such as the renunciation of religion or its shift into the private sphere have not been accessed in a systematic way. Against the backdrop of existing research on migration, religious transformation and non-affiliation, this contribution focuses on privatization and relativization as coequal forms of religious change in the diaspora. Based on a qualitative content analysis of 102 interviews with refugees of various religious affiliation and countries of origin several aspects and mechanisms of the three basic patterns of religious change (intensification, privatization and relativization) will be outlined. The findings suggest that ’experienced‘ religious minorities, such as Yezidis exhibit a pattern of compensating intensification in light of their newly found freedom of religion whereas Muslim refugees tend to religious privatization in response to Islamophobic discourses. Furthermore it becomes apparent that women and younger refugees are inclined to religious relativization. Altogether, the evidence suggest that many refugees desire a more intensive religious life, which is, however, prevented by logistic challenges, such as a lack of native-language communities and restrictions of everyday life.